Analisis Yuridis terhadap Kurangnya Kesiapan Mental pada Pasangan Pernikahan Usia Dini sebagai Faktor Penyebab Ketidakharmonisan Rumah Tangga dan Meningkatnya Perceraian - Ni Wayan Juliartini; Ratna Artha Windari; Suarta, I Wayan (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Early marriage remains a legal and social concern because compliance with the statutory minimum age does not necessarily indicate emotional maturity or readiness to assume marital responsibilities. This study aims to analyze the legal position of insufficient mental readiness among young married couples as a factor contributing to household disharmony and to examine its relationship with economic problems, domestic violence, and divorce. The study employs normative legal research with a descriptive-analytical approach using statutory, conceptual, and literature approaches. Legal materials consist of legislation, court data, books, journal articles, and research findings, which are analyzed qualitatively through deductive reasoning. The study finds that insufficient mental readiness is neither a requirement for the validity of marriage nor an independent legal ground for divorce. Its legal relevance arises when it is manifested in prolonged disputes, neglect of marital obligations, abandonment, or violence. Bali data indicate high numbers of marriage dispensations and divorce cases, although they do not prove a single causal relationship. Economic hardship may intensify family stress, while domestic violence remains a prohibited act with distinct legal consequences. These findings imply the need to strengthen premarital education, psychological readiness assessment, economic planning, and victim protection to prevent household breakdown among couples.